1980
DOI: 10.1002/ijc.2910260218
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of products from necrotic regions of tumours on the in vitro migration of cancer and peritoneal exudate cells

Abstract: The invasion of normal tissues by cancer cells and the infiltration of tumours by macrophages to some degree involves active translatory movements by these cells. As necrosis is a common occurrence in solid tumours, we have studied the interactions of saline extracts from the necrotic regions of rat Walker-256 tumours and mouse Gardner lymphosarcomas on the transmembrane, in vitro migration of Walker and Gardner cancer cells, and rat and mouse peritoneal macrophages. Necrotic extracts enhanced cell migration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous research has shown that the expanding tumor increases both its cell loss (through necrosis/apoptosis and invasion) and its quiescent cell population (G /G arrested) due to a declining gradient of nutritional elements towards the center of the rapidly growing avascular mass (Folkman & Hochberg, 1973;Durand, 1976;Landry et al, 1981;Mueller-Klieser et al, 1986;Rotin et al, 1986;Freyer & Schor, 1989). At advanced tumor stages, volumetric growth slows down mostly due to the declining growth fraction (GF), an increasing cell loss and G -fraction (Turner & Weiss, 1980;Bauer et al, 1982;Freyer & Sutherland, 1985) caused by a lack of nutrition as well as an increasing con"nement pressure.…”
Section: Resultsmentioning
confidence: 96%
“…Previous research has shown that the expanding tumor increases both its cell loss (through necrosis/apoptosis and invasion) and its quiescent cell population (G /G arrested) due to a declining gradient of nutritional elements towards the center of the rapidly growing avascular mass (Folkman & Hochberg, 1973;Durand, 1976;Landry et al, 1981;Mueller-Klieser et al, 1986;Rotin et al, 1986;Freyer & Schor, 1989). At advanced tumor stages, volumetric growth slows down mostly due to the declining growth fraction (GF), an increasing cell loss and G -fraction (Turner & Weiss, 1980;Bauer et al, 1982;Freyer & Sutherland, 1985) caused by a lack of nutrition as well as an increasing con"nement pressure.…”
Section: Resultsmentioning
confidence: 96%
“…apoptosis/ necrosis) linked with an increased level of hostile toxic metabolites per lattice site. For example, it has been demonstrated that low pH inhibits cell proliferation and contributes to cell death and necrosis within solid tumors, which in turn may induce tumor cells to migrate to more favorable locations (Tannock & Rotin, 1989;Turner & Weiss, 1980). In the following section we review some relevant modeling work.…”
Section: Emerging Patterns In Tumor Systemsmentioning
confidence: 98%
“…Aliquots of membranes and cell homogenates were assayed for 5' nucleotidase activity (Douglas et al, 1972), acid phosphatase activity (Turner & Weiss, 1980) and DNA content (Munro & Fleck, 1966). The mean specific activity of 5' nucleotidase from the membrane preparations was 3.5umolh-'mg-' protein, a value that was 5-6 times higher than the specific activity of this enzyme in the homogenate.…”
Section: Control Tissue and Cell Suspensionsmentioning
confidence: 99%